Front Cover: Metal Phosphides as Co‐Catalysts for Photocatalytic and Photoelectrocatalytic Water Splitting (ChemSusChem 22/2017). Issue 22 (14th November 2017) - Cao, Shuang; Wang, Chuan‐Jun; Fu, Wen‐Fu; Chen, Yong
Abstract : The Front Cover shows a representation of a vast universe with a series of transition metal phosphides, which can be explored and used as photochemical and photoelectrochemical water‐splitting co‐catalysts. More information can be found in the Minireview by Cao et al. onpage 4306 in Issue 22, 2017 (DOI:10.1002/cssc.201701450 ).